Advances in Cost-Efficient Thin-Film Photovoltaics Based on Cu(In, Ga)Se2. (August 2017) - Powalla, Michael; Paetel, Stefan; Hariskos, Dimitrios; Wuerz, Roland; Kessler, Friedrich; Lechner, Peter; Wischmann, Wiltraud; Friedlmeier, Theresa Magorian
Abstract: In this article, we discuss the leading thin-film photovoltaic (PV) technology based on the Cu(In, Ga)Se2 (CIGS) compound semiconductor. This contribution includes a general comparison with the conventional Si-wafer-based PV technology and discusses the basics of the CIGS technology as well as advances in world-record-level conversion efficiency, production, applications, stability, and future developments with respect to a flexible product. Once in large-scale mass production, the CIGS technology has the highest potential of all PV technologies for cost-efficient clean energy generation.